Cognitive Ability and Personality Profile of Graduate Students vis-à-vis Their Academic Achievement - Gloria B. Abrazado; Ralyn B. Rodriguez (Future Science / FSH-PH Publications, 2026)
This study intended to correlate academic achievement of the graduate students with their cognitive ability and personality profile. Descriptive-correlational design was utilized with a total of 24 participants from one private Graduate School, who met the inclusion criteria set in this research. Frequency, percentage, rank, mean and Spearman rho correlation test were used for data analysis. Results show that the majority of the participants demonstrate superior to excellent academic performance in their discipline and the majority have average cognitive abilities based on the MD5 mental ability test. Results further reveal that the majority of the participants are average across personality traits based on Cattell’s 16 PF which suggest that they generally possess a well-rounded and balanced approach to their academic and personal lives. It was found in this study that the academic achievement of the participants is not significantly correlated with their cognitive ability and personality profile which may indicate that variations in graduate students’ performance may be influenced by factors beyond cognitive ability and measured personality traits, such as motivation and professional experience. The results of the study imply the need of the Graduate School to enhance the average levels of various personality traits by providing opportunities for personal growth, support, and development for graduate students.